The Prevalence of Hypomagnesemia in Critically Ill Patients Admitted in Medically Intensive Care Unit - Maryam Farhan Baloch; Azeem Khalid; Kiran Naimat; Muhammad Usman Khalid; Muhammad Abdul Khaliq Khan; Shahzaib Maqbool (International Journal of Medical Students, 2023)
Background